Synthesis of Triazole‐Containing rctt Tetra‐C‐Naphthyl‐Calix [4]resorcinarene and 1, 1‐Dinaphthylmethane Derivatives. Issue 39 (16th October 2020) - Serkova, Olga S.; Glushko, Valentina V.; Toropygin, Ilya Yu.; Maslennikova, Vera I.
Abstract: rctt‐ Octatriazolyl‐ ortho ‐methyl‐tetra‐ C ‐naphthyl‐calix[4]resorcinarenes containing triazole moieties on the horizontally and vertically arranged benzene rings of the macrocyclic core; rctt tetra‐triazolyl‐tetra‐phosphato‐ ortho ‐methyl‐tetra‐ C ‐naphthyl‐calix[4]resorcinarene with triazole groups being bound only to the vertically arranged benzene rings of the macrocycle and the phosphate groups being immobilized on the horizontally arranged benzene rings; di‐ and tetra‐triazolyl‐dinaphthylmethanes differing in the number and spatial orientation of chelate pairs; and 2, 2′‐diphosphonato‐dinaphthylmethanes in which exocyclic substituents include the phosphonate and the terminal triazole moieties connected by linkers differing in the steric crowding were synthesized, isolated in high yields, and characterized. In all cases, the catalytic azide‐alkyne cycloaddition click reaction was the key step of the synthesis. One octatriazole calix[4]resorcinarene derivative was subjected to subsequent transformations in which the terminal ester groups in the triazole rings were converted to carboxyl and amide groups. The alkylation of rctt resorcinarenes with propargyl bromide and modification of octatriazole resorcinarene derivative with terminal ester groups by biologically active phenethylamine proceeded efficiently only under microwave irradiation. Abstract : Routes for synthesis of triazole‐containing derivatives of rctt ortho ‐methyl‐tetra‐ C ‐naphthyl‐calix[4]resorcinarene, di‐ and tetrahydroxy‐dinaphthylmethanes were developed. A series of new polyfunctional compounds differing in number of transformable branches, nature and structure of the polycyclic platform, spacers between aromatic ring and heterocycle, terminal substituents in the triazole rings was obtained.